Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
the development of the vocational education system is implemented as a state idea and a state project. The essence of the system of practice-oriented training is the competence approach, and an obligatory component of the system of practice-oriented training is the institutionalization of the process – active work on career guidance of students – in the design, planning and implementation of gradually increasing complexity of practical tasks-projects.
Keywords: инклюзивное образование; компетентностный подход; competence approach; глобальная автоматизация труда; развитие системы профессионального образования; образовательные инновации; образовательная инфраструктура; кадровые ресурсы; практикоориентированное обучение; global automation of labor; development of the system of professional education; educational innovations; educational infrastructure; human resources; inclusive education; practice-oriented training